θ-centralizers on semiprime Banach *-algebras - Nikoufar, I.; Rassias, Th.M. (Український математичний журнал, 2014)
We generalize the celebrated theorem of Johnson and prove that every left θ -centralizer on a semisimple Banach algebra with left approximate identity is continuous. We also investigate the generalized Hyers–Ulam–Rassias stability and the superstability of θ -centralizers on semiprime Banach *-algebras. Шляхом узагальнення відомої теореми Джонсона доведено, що кожний лівий 0-централізатор на напівпростій банаховій алгебрі з лівою наближеною одиницею є неперервним. Також досліджено узагальнену стійкість Хайерса-Улама-Рассіаса та надстійкість θ-централізаторів на напівпростих *-алгебрах.